Comprehensive understanding of the adverse effects associated with temozolomide: a disproportionate analysis based on the FAERS database - Zhou, Yusen; Jia, Peng; Fang, Yuting; Zhu, Wei; Gong, Yong; Fan, Tianyu; Yin, Jiangliu (Frontiers in Pharmacology, 2024)
Background: Temozolomide, which is the standard drug for glioma treatment, has several adverse effects (AEs) in the treatment of gliomas and other tumors that are not yet fully understood. This is due to the pharmacological nature of the alkylating agent. A significant proportion of these effects have not been systematically documented or reported. Methods: We selected data from the United States FDA Adverse Event Reporting System (FAERS) database from the first quarter of 2004 to the fourth quarter of 2023. Four algorithms were used for disproportionate analysis, with the objective of assessing the association between temozolomide and related adverse events. Results: In this study, 20079906 case reports were collected from the FAERS database, of which 15152 adverse events related to temozolomide were reported. A total of 352 preferred terms (PTs) and 24 system organ classes (SOCs) that were significantly disproportionally related to the four algorithms were included. The SOCs included blood and lymphatic system disorders (χ2=18220.09, n=4325); skin and subcutaneous tissue disorders (χ2=408.06, n=1347); investigations (χ2=639.44, n=3925); musculoskeletal and connective tissue disorders (χ2=1317.29, n=588); and psychiatric disorders (χ2=1098.47, n=877). PT levels were screened for adverse drug reaction signals consistent with drug inserts, such as anemia, thrombocytopenia, liver function abnormalities, nausea and vomiting, as well as rarely reported adverse drug reactions, such as aplastic anemia, myelodysplastic syndromes, electrolyte disorders, cerebral edema, and high-frequency mutations.The results of our investigation demonstrated both adverse effects that had been reported and a multitude of unreported adverse effects that were serious in nature and lacked a clear cause. These novel findings suggest that more attention should be given to the clinical conditions of patients after treatment to provide a more comprehensive perspective and understanding for further clarifying the safety of temozolomide.